1997
DOI: 10.1111/j.2042-7158.1997.tb06103.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioadhesive Microspheres for Ophthalmic Administration of Acyclovir

Abstract: The bioavailability of acyclovir to the ophthalmic epithelium is low and when the drug is administered in ophthalmic ointment it must be applied every four hours. An emulsification technique has been used to prepare acyclovir-loaded chitosan microspheres with the aim of promoting the prolonged release of drug and increasing its ocular bioavailability. The microparticulate drug-delivery systems obtained have been characterized for their morphology and physicochemical characteristics by in-vitro dissolution test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(59 citation statements)
references
References 15 publications
2
53
1
3
Order By: Relevance
“…In this study, the X-ray patterns of the pure drug and the polymer are shown in Figure 4. The X-ray pattern of Eudragit S 100 showed a halo pattern (Figure 4f) indicating its existence in amorphous form, whereas that of acyclovir exhibited crystalline characteristics, as shown in Figure 4g identical to that reported by Genta et al (1997). The X-ray patterns of microspheres prepared by using different amounts of acyclovir can be seen in Figure 4a-4e), which showed a combined pattern of those of the polymer and the pure drug.…”
Section: Powder X-ray Diffractionsupporting
confidence: 54%
See 2 more Smart Citations
“…In this study, the X-ray patterns of the pure drug and the polymer are shown in Figure 4. The X-ray pattern of Eudragit S 100 showed a halo pattern (Figure 4f) indicating its existence in amorphous form, whereas that of acyclovir exhibited crystalline characteristics, as shown in Figure 4g identical to that reported by Genta et al (1997). The X-ray patterns of microspheres prepared by using different amounts of acyclovir can be seen in Figure 4a-4e), which showed a combined pattern of those of the polymer and the pure drug.…”
Section: Powder X-ray Diffractionsupporting
confidence: 54%
“…• C. The DSC thermogram obtained from this study slightly differed from the studies by Genta et al (1997) and Kristl et al (1996) indicating that the DSC curve of acyclovir exhibited a small melting endothermic peak at approximately 170…”
Section: Differential Scanning Calorimetrycontrasting
confidence: 44%
See 1 more Smart Citation
“…Liposomes were able to delay the release of glycolic acid, and microspheres were unable to modulate active substance release even following crosslinking with glutaraldehyde, a compound causing a reduction of microsphere sizes. In previous studies, Genta et al (1997) were able to modulate the release of the acyclovir, a lypophilic drug, using chitosan microspheres with mean diameter ≤ 25 µm for ocular administration.…”
Section: Resultsmentioning
confidence: 99%
“…71,81 A quitosana exibe comportamento biológico favorável, tais como bioadesão, permeabilidade e características fisico-químicas interessantes, que tornam este biopolímero um material único para design de sistemas de liberação de fármaco ocular. [82][83][84][85] A quitosana é considerada um bom sistema de liberação de fármacos na cavidade bucal, visto que a sua atividade antibacteriana pode ser devida às interações eletrostáticas entre grupos amino e grupos aniônicos nas paredes celulares das bactérias provenientes de resíduos de ácidos carboxílicos e fosfolipídeos. 86 Sistemas de liberação bucal mucoadesivos desenvolvidos por hidrogéis de quitosana parecem ser apropriados para prolongar o tempo de residência da forma farmacêutica, melhorando o efeito terapêutico no tratamento de infecções localizadas, tais como doença periodontal e estomatite.…”
Section: Sistemas De Liberação De Fármacos a Partir De Matrizes De Quunclassified